2013
DOI: 10.1074/jbc.m113.486670
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of GdFFD, a d-Amino Acid-containing Neuropeptide That Functions as an Extrinsic Modulator of the Aplysia Feeding Circuit

Abstract: Background: L-to-D conversion of an amino acid in a neuropeptide can be required for bioactivity. Results: A new D-amino acid-containing peptide (DAACP), GdFFD, shows stereospecific bioactivity in the feeding circuit. Conclusion: Our findings broaden the importance of this unusual post-translational modification, providing new methods to accelerate DAACP discovery. Significance: GdFFD is the first DAACP showing bioactivity in a well defined circuit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
108
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(118 citation statements)
references
References 82 publications
6
108
0
4
Order By: Relevance
“…5,6 In neuropeptides, this involves the enzymatic conversion of one residue near the N-terminus from an l -amino acid to a d -amino acid. 5,713 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 In neuropeptides, this involves the enzymatic conversion of one residue near the N-terminus from an l -amino acid to a d -amino acid. 5,713 …”
mentioning
confidence: 99%
“…6 One way to overcome this difficulty is via the use of MS/MS-based techniques and comparing peptides with only l -amino acids to their DAACP epimers. 7,1418 Recently, MALDI-TOF/TOF was used for the discovery of d -Leu in the peptide GH-2. 19 This study also established a stereosensitive fragmentation effect of d -amino acids from various amino acid classes on different peptide sequences, which can aid in the discovery of DAACPs through MALDI-TOF/TOF by observing the fragmentation ratios of specific peptides.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The enantioseparation can then be carried out directly, by so-called enantioselective chromatography [27], or indirectly via the generation of diastereomers through derivatization with enantiomerically pure reagents followed by achiral chromatography [6]. Furthermore, Bai et al reported a technique of directly separating diastereomeric DAACPs by applying MALDI TOF/TOF measurements, yielding significantly different fragmentation patterns [23,28].…”
Section: Introductionmentioning
confidence: 97%
“…Even more specifically, DAACPs have been shown to represent a very specific form of posttranslational modification and to play an important role in cell signaling pathways [20][21][22][23]. The partial isomerization of certain AAs in all l-AA containing peptides has been shown to drastically alter the peptides' biological activities [22].…”
Section: Introductionmentioning
confidence: 99%